Removal of Hg(II) from Aqueous Solution Using Graphene Oxide as Highly Potential Adsorbent - Nuengmatcha, Prawit; Mahachai, Ratana; Chanthai*, Saksit (Asian Journal of Chemistry, 2014)
Mercury and its compounds are neurotoxins, which simply cause any blockage of enzyme sites and interfere in related protein synthesis and generally found as much toxic metal contaminants in wastewater and environment. Removal of such metal ions by various adsorbents including chitosan, resins, ash, silica gel and activated carbon was reported. Presently, graphene oxide is one of the highly potential adsorbents used in numerous applications. Its main advantage consists of three main functional groups (carbonyl, hydroxyl and epoxide) on their surface giving anchored sites for metal ions complexation, namely for adsorption capabilities of Pb(II), Zn(II), Cu(II), Cd(II) and Co(II). The present study was thus subject to the adsorption of Hg(II) with graphene oxide compared with bare graphite. For an optimization study, the effects of pH solution (2-9), incubation time (10-240 min) and an initial concentration of Hg(II) (0.1-60 mg/L) were investigated. Mercury(II) ion was analyzed by FI-HGAAS. From the results, the adsorption capacity for Hg(II) removal from aqueous solution was 50.51 mg/g at pH 4.4 and their adsorption state was completed within 80 min. While bare graphite gave the adsorption capacity of 22.94 mg Hg(II)/g at pH 6.5 within 100 min. The adsorption isotherms of Hg(II) fit well with the Langmuir and Freundlich models for graphene oxide and bare graphite, respectively. It is demonstrated that graphene oxide can also be a highly potential adsorbent for toxic metals.